Agroforestry in Kenya is supporting both climate adaptation and mitigation - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
In the Nyando basin in Western Kenya, climate change and variability are already evident. Droughts, floods and unpredictable rainfall have increased, affecting agriculture and food security. CCAFS East Africa is working with partners in Western Kenya to test a portfolio of interventions that will help farmers to address climate risks and food insecurity. Agro-forestry, land and water management are among the mitigation interventions employed to reduce greenhouse gas emissions in Nyando basin. Agroforestry for carbon rich landscapes is one of the mitigation activities being implemented. Read more about - Empowering a local community to address climate risks and food insecurity in Lower Nyando, Kenya - http://cgspace.cgiar.org/handle/10568/27889